Supported catalyst for acidic oxygen evolution reaction as well as preparation method and application of supported catalyst
By using a method of loading precious metals and/or precious metal oxides with specific sizes, the problem of insufficient catalyst activity and stability under low precious metal loads in the prior art is solved, and high efficiency in acid oxygen evolution reactions are achieved. Stable catalytic performance.
Patent Information
- Application Number
- CN202411408490.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to obtain catalysts with excellent activity and stability in acidic oxygen evolution reactions under low precious metal loads, which seriously hinders the large-scale application of proton exchange membrane water electrolytic cell (PEMWE).
The MnO2 nanofiber of specific size is used as a carrier to carry precious metals and/or precious metal oxides, and the size of MnO2 nanofibers is controlled by the introduction of potassium sulfate and the heating reaction temperature. The particle size of the MnO2 nanofibers is formed on the surface of the carrier by molten salt method. And precious metal oxides with good dispersion.
Under the low loading of precious metals, the supported catalyst exhibits excellent catalytic performance and stability, can effectively catalyze the oxygen precipitation reaction and proton exchange membrane to produce hydrogen by electrolysis, and maintain high efficiency and stability during long-term operation.
Smart Images

Figure CN119465262A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation and electrocatalysis, and in particular to a supported catalyst for acidic oxygen evolution reaction and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolyzer (PEMWE) has a high current density (≥1A·cm -2 ), high hydrogen purity (>99.99%), strong flexibility (<5s), and the ability to adapt well to the intermittent nature of renewable energy make it an ideal green hydrogen production technology. However, the lack of efficient and inexpensive acidic oxygen evolution reaction (OER) catalysts has seriously hindered its large-scale application. At present, the main challenge of PEMWE is to obtain Ir-based catalysts with excellent activity and stability at relatively low Ir loadings.
[0003] The current effective strategy is to anchor the iridium-based catalyst on a conductive and acid-resistant carrier to promote the exposure of active sites. For example, patent CN115896841A discloses a core-shell catalyst of iridium-loaded metal oxide. The core-shell catalyst does not use precious metal iridium as the main structure, but uses inner core metal oxide as the carrier, which can greatly reduce the amount of precious metal iridium and reduce costs, but its preparation process is complicated and involves the use of surfactants; patent CN114808020ACN114808020A is a long-life supported oxygen evolution reaction electrocatalyst, which uses two-dimensional hexagonal boron nitride with high electrochemical stability as a carrier to load precious metals. Although the utilization efficiency of precious metals has been improved, the catalytic stability is not outstanding. In addition, carbon materials commonly used as conductive carriers have poor stability in the highly oxidizing environment of the anode, so catalysts loaded with precious metals as carriers are not suitable for use as OER catalysts.
[0004] Based on this, finding a suitable carrier so that the prepared supported catalyst can have both excellent catalytic activity and stability at a low precious metal loading will help promote the commercialization of PEMWE. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a supported catalyst for acidic oxygen evolution reaction and a preparation method and application thereof, wherein the electrocatalyst comprises MnO 2 Nanofiber carrier and loaded on MnO 2 The noble metal and / or noble metal oxide on the nanofiber carrier, under the condition of low noble metal loading, the supported catalyst shows excellent catalytic performance and stability in electrocatalytic oxygen evolution reaction and proton exchange membrane water electrolysis to produce hydrogen.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a supported catalyst for acidic oxygen evolution reaction, wherein the supported catalyst comprises MnO 2 Nanofiber support and MnO loaded 2 Active particles on the surface of the nanofiber carrier; the active particles contain noble metals and / or noble metal oxides; the MnO 2 The length of the nanofiber carrier is 100-800nm and the width is greater than 20nm.
[0008] Furthermore, the MnO 2 The length of the nanofiber carrier is preferably 200-600 nm, more preferably 200-500 nm; the MnO 2 The width of the nanofiber support is preferably 30-80 nm.
[0009] Furthermore, the particle size of the active particles is less than 2 nm, and the active particles can be stably loaded on the above MnO 2 On the nanofiber carrier, the catalyst exhibits high catalytic activity and excellent stability with low noble metal content; in some preferred embodiments, the particle size of the active particles is in the range of 1.5-1.9 nm.
[0010] Furthermore, the mass fraction of the active particles in the supported catalyst is preferably 10wt%-40wt%. Within this dosage range, the active particles have good dispersibility and can be stably combined with the carrier to form an interface, thereby improving the utilization rate of the precious metal and the stability of the catalyst.
[0011] Furthermore, the noble metal is selected from one or more of iridium, ruthenium and platinum; and the noble metal oxide is iridium dioxide and / or ruthenium dioxide.
[0012] The second aspect of the present invention provides a method for preparing the supported catalyst according to the first aspect, comprising the following steps:
[0013] (1) Dispersing a manganese source, ammonium persulfate and potassium sulfate in a first solvent and heating the mixture to obtain MnO 2 Nanofibers;
[0014] (2) MnO 2 The nanofibers are uniformly mixed with the noble metal source dispersion and the molten salt, and then dried to obtain a mixed powder, which is then calcined in an inert atmosphere to obtain the supported catalyst.
[0015] Furthermore, in step (1), the manganese source is selected from one or more of manganese sulfate and its hydrate, potassium permanganate, manganese chloride, manganese nitrate, and manganese carbonate.
[0016] Furthermore, in step (1), the first solvent is selected from one or more of water, ethanol, acetone, ethylene glycol, and isopropanol.
[0017] Furthermore, in step (1), the mass ratio of the manganese source, ammonium persulfate and potassium sulfate is 1:(1.35-2):(2.29-4).
[0018] Furthermore, in step (1), the temperature of the heating reaction is 130-150° C.; and the time of the heating reaction is 2-20 hours.
[0019] Furthermore, in step (2), the noble metal source dispersion is obtained by dispersing the noble metal source in a second solvent; the noble metal source is preferably one or more of iridium trichloride, iridium tetrachloride, potassium iridium chloroate, sodium iridium chloroate, iridium nitrate, tetrairidium dodecacarbonyl and hydrates of the above compounds; the second solvent is preferably one or more of water, ethanol, acetone, ethylene glycol, isopropanol and N-methylpyrrolidone.
[0020] Further, in step (2), the molten salt is preferably one or more of sodium nitrate, potassium nitrate, potassium hydroxide, sodium hydroxide, potassium chloride, sodium chloride, potassium sulfate, and potassium carbonate; more preferably, the mass ratio of the noble metal source to the molten salt in the noble metal dispersion is (0.028-0.1112): 1. The introduction of the molten salt can penetrate between the generated particles and prevent the particles from being connected to each other, so that the prepared noble metal / noble metal oxide has a fine particle size and good dispersibility; and the added molten salt can be fully removed by washing with water, and will not affect the purity of the product.
[0021] Furthermore, in step (2), the drying temperature is preferably 50-100° C., and the drying time is preferably 1-5 h.
[0022] Furthermore, in step (2), the calcination temperature is preferably 300-500° C., and the calcination time is preferably 1-5 h.
[0023] The third aspect of the present invention provides an application of the supported catalyst described in the first aspect or the supported catalyst prepared by the preparation method described in the second aspect in catalyzing oxygen evolution reaction and hydrogen production by proton exchange membrane water electrolysis.
[0024] Furthermore, the catalytic oxygen evolution reaction and proton exchange membrane water electrolysis to produce hydrogen both include a working electrode, and the supported catalyst is used to prepare a coating of the working electrode.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a supported catalyst comprising MnO 2Nanofiber carrier and loaded on MnO 2 The noble metal and / or noble metal oxide on the nanofiber carrier exhibits excellent electrocatalytic performance and electrochemical stability under the condition of low noble metal loading, and can be used to catalyze oxygen evolution reaction and proton exchange membrane water electrolysis to produce hydrogen. Among them, the supported catalyst with a noble metal content of 20.5wt% is used for oxygen evolution reaction, and the electrochemical stability is 10mA·cm -2 At a current density of 10 mA cm, the OER overpotential is only 300 mV, and at a current density of 10 mA cm -2 The voltage decay rate was only 0.96 μV / h when the current density was 1 A·cm -2 The device ran at a high current density for 25 hours without significant change in potential, demonstrating excellent stability.
[0027] In addition, the present invention also provides a method for preparing the above-mentioned supported catalyst, by introducing potassium sulfate and controlling the heating reaction temperature, the MnO 2 The size of the nanofibers is controlled, and a small, uniform and well-dispersed noble metal oxide is formed on the surface of the carrier by a molten salt method, thereby obtaining a supported catalyst with high catalytic activity and good stability. The above preparation method is simple to operate and has good controllability, and is suitable for batch preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 TEM image of the supported catalyst prepared in Example 1;
[0029] Figure 2 TEM image of the supported catalyst prepared in Example 1
[0030] Figure 3 TEM image of the supported catalyst prepared in Comparative Example 1;
[0031] Figure 4 The supported catalyst prepared in Example 1 and Comparative Example 1 was used as an electrocatalyst in 0.5 MH 2 SO 4 The constant current chronopotentiograph in;
[0032] Figure 5 This is a diagram showing the catalytic stability of the supported catalyst prepared in Example 1 as an electrocatalyst in the oxygen evolution reaction. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] Example 1
[0036] This embodiment relates to the preparation of a supported catalyst, and the specific operations are as follows:
[0037] (1) 3.38 g MnSO 4 ·H 2 O(AR), 4.564g(NH 4 ) 2 S 2 O 8 (AR) and 10.4556gK 2 SO 4 (AR) was dissolved in 70 mL H 2 O. After vigorous stirring for 1 hour, the mixture was transferred to a reactor and heated at 140 °C for 12 hours. After cooling to room temperature, it was washed with deionized water 5 times and dried in an oven at 80 °C overnight to obtain MnO 2 Nanofibers (fiber width 30-80nm, specific surface area 74.8m 2 / g);
[0038] (2) 55.6 mg K 2 IrCl 6 Dissolve in ethanol and then add 1g NaNO 3 and 50 mg MnO 2 The suspension was ultrasonically dispersed for 30 min and then dried at 90 °C for 5 h. The mixed powder was then ground and heated in a tubular furnace at a rate of 5 °C / min under N 2 The mixture was heated to 350°C in a gas atmosphere and kept at this temperature for 1 hour. After cooling to room temperature, it was washed with deionized water and ethanol to remove excess salt and impurities, and then dried in an oven at 60°C to obtain 2 Iridium dioxide on the surface of nanofibers.
[0039] In this example, the obtained MnO 2 The iridium dioxide composite electrocatalyst on the surface of nanofibers was characterized by TEM, such as Figure 1 MnO 2 The length of the nanofibers is 100-800nm, the width is in the range of 30-80nm, and the iridium dioxide is evenly dispersed in the MnO 2The surface of nanofibers has good particle size uniformity, about 1.7nm ( Figure 2 ).
[0040] Example 2
[0041] This embodiment relates to the preparation of a supported catalyst, and the specific operations are as follows:
[0042] (1) 3.38 g MnSO 4 ·H 2 O(AR), 4.564g(NH 4 ) 2 S 2 O 8 (AR) and 10.4556gK 2 SO 4 (AR) was dissolved in 70 mL H 2 O. After vigorous stirring for 1 hour, the mixture was transferred to a reactor and heated at 140 °C for 12 hours. After cooling to room temperature, it was washed with deionized water 5 times and dried in an oven at 80 °C overnight to obtain MnO 2 Nanofibers (fiber width 30-80nm, specific surface area 74.8m 2 / g);
[0043] (2) 111.2 mg K 2 IrCl 6 Dissolve in ethanol and then add 1g NaNO 3 and 50 mg MnO 2 The suspension was ultrasonically dispersed for 30 min and then dried at 90 °C for 5 h. The mixed powder was then ground and heated in a tubular furnace at a rate of 5 °C / min under N 2 The mixture was heated to 350°C in a gas atmosphere and kept at this temperature for 1 hour. After cooling to room temperature, it was washed with deionized water and ethanol to remove excess salt and impurities, and then dried in an oven at 60°C to obtain 2 Iridium dioxide on the surface of nanofibers.
[0044] Example 3
[0045] This embodiment relates to the preparation of a supported catalyst, and the specific operations are as follows:
[0046] (1) 3.38 g MnSO 4 ·H 2 O(AR), 4.564g(NH 4 ) 2 S 2 O 8 (AR) and 10.4556gK 2 SO 4(AR) was dissolved in 70 mL H 2 O. After vigorous stirring for 1 hour, the mixture was transferred to a reactor and heated at 140 °C for 12 hours. After cooling to room temperature, it was washed with deionized water 5 times and dried in an oven at 80 °C overnight to obtain MnO 2 Nanofibers (fiber width 30-80nm, specific surface area 74.8m 2 / g);
[0047] (2) 28 mg K 2 IrCl 6 Dissolve in ethanol and then add 1g NaNO 3 and 50 mg MnO 2 The suspension was ultrasonically dispersed for 30 min and then dried at 90 °C for 5 h. The mixed powder was then ground and heated in a tubular furnace at a rate of 5 °C / min under N 2 The mixture was heated to 350°C in a gas atmosphere and kept at this temperature for 1 hour. After cooling to room temperature, it was washed with deionized water and ethanol to remove excess salt and impurities, and then dried in an oven at 60°C to obtain 2 Iridium dioxide on the surface of nanofibers.
[0048] Comparative Example 1
[0049] This comparative example relates to the preparation of a supported catalyst, and the specific operation is as follows:
[0050] (1) 0.85 g MnSO 4 ·H 2 O(AR), 1.14g(NH 4 ) 2 S 2 O 8 (AR) was dissolved in 40 mL H 2 O. After vigorous stirring for 1 hour, the mixture was transferred to a reactor and heated at 140 °C for 12 hours. After cooling to room temperature, it was washed with deionized water 5 times and dried in an oven at 80 °C overnight to obtain MnO 2 Nanorods (length 1-2 μm, width 200-500 nm, specific surface area 40 m 2 / g);
[0051] (2) 55.6 mg K 2 IrCl 6 Dissolve in ethanol and then add 1g NaNO 3 and 50 mg MnO 2 The suspension was ultrasonically dispersed for 30 min and then dried at 90 °C for 5 h. The mixed powder was then ground and heated in a tubular furnace at a rate of 5 °C / min under N2 The mixture was heated to 350°C in a gas atmosphere and kept at this temperature for 1 hour. After cooling to room temperature, it was washed with deionized water and ethanol to remove excess salt and impurities, and then dried in an oven at 60°C to obtain 2 Iridium dioxide on the surface of nanorods.
[0052] Comparative Example 2
[0053] This comparative example relates to the preparation of a supported catalyst, and the specific operation is as follows:
[0054] (1) 0.775 g MnSO 4 ·H 2 O(AR), 1.14g(NH 4 ) 2 S 2 O 8 (AR) was dissolved in 40 mL H 2 O. After vigorous stirring for 1 hour, the mixture was transferred to a reactor and heated at 90 °C for 12 hours. After cooling to room temperature, it was washed with deionized water 5 times and dried in an oven at 80 °C overnight to obtain MnO 2 Sea urchin-shaped nanorods (length 1-2 μm, width 200-500 nm, specific surface area 52 m 2 / g);
[0055] (2) 55.6 mg K 2 IrCl 6 Dissolve in ethanol and then add 1g NaNO 3 and 50 mg MnO 2 The suspension was ultrasonically dispersed for 30 min and then dried at 90 °C for 5 h. The mixed powder was then ground and heated in a tubular furnace at a rate of 5 °C / min under N 2 The mixture was heated to 350°C in a gas atmosphere and kept at this temperature for 1 hour. After cooling to room temperature, it was washed with deionized water and ethanol to remove excess salt and impurities, and then dried in an oven at 60°C to obtain 2 Iridium dioxide on the surface of sea urchin-shaped nanorods.
[0056] Comparative Example 3
[0057] This comparative example involves the preparation of a supported catalyst. The only difference from Example 1 is the reaction temperature, which is 120°C. Manganese dioxide nanofibers with a fiber width of 10-20 nm and a specific surface area of 90 m 2 / g. The rest of the operations were the same as in Example 1, and a supported catalyst of manganese dioxide nanofiber supported iridium dioxide was prepared.
[0058] Comparative Example 4
[0059] This comparative example relates to the preparation of iridium dioxide nanoparticles, and the specific operation is as follows:
[0060] 55.6 mg K 2 IrCl 6 Dissolve in ethanol and then add 1g NaNO 3 The suspension was ultrasonically dispersed for 30 min and then dried at 90 °C for 5 h. The mixed powder was then ground and heated in a tubular furnace at a rate of 5 °C / min under N 2 The mixture was heated to 350°C in an atmosphere and kept at this temperature for 1 hour. After cooling to room temperature, it was washed with deionized water and ethanol to remove excess salt and impurities, and dried in an oven at 60°C to obtain pure iridium dioxide nanoparticles.
[0061] The TEM images of the iridium dioxide nanoparticles prepared in this comparative example are as follows: Figure 3 As shown, the particle size of iridium dioxide is much larger than that of MnO 2 Iridium oxide particles on the surface of nanofibers ( Figure 2 ), indicating that MnO 2 The nanofiber carrier is beneficial to the dispersion and anchoring of iridium oxide particles.
[0062] Performance Testing
[0063] 1. The supported catalysts or iridium dioxide nanoparticles prepared in the above examples and comparative examples are used as electrocatalysts in OER, and the specific operations are as follows:
[0064] The OER electrocatalytic test was carried out using a CHI660e electrochemical workstation with a standard three-electrode system. 3 mg of the supported catalyst or iridium dioxide nanoparticles prepared in Examples 1-3 and Comparative Examples 1-4 were added with 300 μL of deionized water, 300 μL of ethanol and 30 μL of a mixed solution of 5 wt.% Nafion, and ultrasonically dispersed for 1 h to obtain a uniform slurry. The slurry was dripped onto a 3 cm 2 After the slurry is dried, the loading amount is 1 mg / cm 2 The working electrode was selected as the carbon rod electrode, the saturated calomel electrode was selected as the reference electrode, and the 0.5 mol / L sulfuric acid solution was selected as the electrolyte. The linear polarization curve of the oxygen evolution reaction was obtained at a scanning speed of 5 mV / s.
[0065] The test results are shown in Table 1 below:
[0066] Table 1
[0067]
[0068]
[0069] As shown in Table 1, in Examples 1-3, the MnO 2 The supported catalyst prepared by using nanofiber as carrier to load iridium dioxide showed excellent catalytic activity in the catalytic oxygen evolution reaction. The supported catalysts prepared in Examples 1 and 2 showed excellent catalytic activity at 10 mA / cm 2 The overpotentials of the catalysts are all lower than those of the pure iridium dioxide catalyst prepared in Comparative Example 4. In addition, it can be seen from Examples 1-3 that too high or too low iridium dioxide loading in the catalyst will affect the catalytic activity of the catalyst, wherein the catalyst prepared in Example 1 with an iridium dioxide loading of about 20 wt% exhibits the best catalytic activity, which is significantly better than the catalytic activity of the pure iridium dioxide catalyst prepared in Comparative Example 4.
[0070] It can be seen from Example 1 and Comparative Examples 1-3 that when the loading amount of precious metal oxide is similar, using MnO 2 Nanofibers as carriers can couple iridium oxide catalysts to achieve optimal catalytic performance, while MnO 2 The performance of the catalyst prepared by nanofiber carrier-supported iridium dioxide is relatively low. 2 The morphology of the carrier will affect the dispersion of the catalyst on its surface, and thus affect the catalytic performance of the catalyst.
[0071] 2. Taking the supported catalyst prepared in Example 1 as an example, an electrochemical workstation was used to record the working current density of 10 mA / cm in the three-electrode electrolytic cell. 2 The working potential changes after 80 hours of continuous operation.
[0072] The supported catalyst prepared in Example 1 was used as the working electrode to perform a half-cell water electrolysis stability test. Figure 5 As shown, at 10mA / cm 2 It can operate stably for more than 80 hours at a current density of , reaching the leading level in the supported catalyst industry. This also proves that the supported catalyst prepared by the present invention has good application prospects in acidic water electrolysis.
[0073] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A supported catalyst for acidic oxygen evolution reaction, characterized in that: The supported catalyst comprises a MnO2 nanofiber carrier and active particles supported on the surface of the MnO2 nanofiber carrier; the active particles contain noble metals and / or noble metal oxides; the MnO2 nanofiber carrier has a length of 100-800nm and a width greater than 20nm.
2. The supported catalyst according to claim 1, characterized in that The particle size of the active particles is less than 2 nm; The mass fraction of the active particles in the supported catalyst is 10wt%-40wt%; The noble metal is selected from one or more of iridium, ruthenium and platinum; The noble metal oxide is iridium dioxide and / or ruthenium dioxide; The width of the MnO2 nanofiber carrier is 30-80nm.
3. A method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) dispersing a manganese source, ammonium persulfate and potassium sulfate in a first solvent and heating the mixture to react to obtain MnO2 nanofibers; (2) The MnO2 nanofibers are uniformly mixed with a noble metal source dispersion and a molten salt, and a mixed powder is obtained after drying. The mixed powder is calcined in an inert atmosphere to obtain the supported catalyst.
4. The preparation method according to claim 3, characterized in that: In step (1), the manganese source is selected from one or more of manganese sulfate and its hydrate, potassium permanganate, manganese chloride, manganese nitrate, and manganese carbonate; The first solvent is selected from one or more of water, ethanol, acetone, ethylene glycol, and isopropanol.
5. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the manganese source, ammonium persulfate and potassium sulfate is 1:(1.35-2):(2.29-4).
6. The preparation method according to claim 3, characterized in that: In step (1), the heating reaction temperature is 130-150° C. and the heating reaction time is 2-20 h.
7. The preparation method according to claim 3, characterized in that: In step (2), the noble metal source dispersion is obtained by dispersing the noble metal source in a second solvent; The noble metal source is selected from one or more of iridium trichloride, iridium tetrachloride, potassium iridium chloroate, sodium iridium chloroate, iridium nitrate, tetrairidium dodecacarbonyl and hydrates of the above compounds; The second solvent is selected from one or more of water, ethanol, acetone, ethylene glycol, isopropanol, and N-methylpyrrolidone.
8. The preparation method according to claim 3, characterized in that: In step (2), the molten salt is selected from one or more of sodium nitrate, potassium nitrate, potassium hydroxide, sodium hydroxide, potassium chloride, sodium chloride, potassium sulfate, and potassium carbonate; The ratio of the mass of the precious metal source in the precious metal dispersion to the mass of the molten salt is (0.028-0.1112):
1.
9. The preparation method according to claim 3, characterized in that: In step (2), the drying temperature is 50-100° C. and the drying time is 1-5 h; The calcination temperature is 300-500°C, and the calcination time is 1-5h.
10. Use of the supported catalyst according to claim 1 or 2 or the supported catalyst prepared by the preparation method according to any one of claims 3 to 9 in catalyzing oxygen evolution reaction and hydrogen production by proton exchange membrane water electrolysis.
Citation Information
Cited By
Supported noble metal oxide cluster catalyst, method of preparation and use thereof in electrolysis of water
CN122687260A